Self made device by rural Nepalese women for pelvic organ prolapse worn for more than a decade: A constant source of vaginal discharge - Pant, Padam Raj (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Complete disappearances of prolapse after the removal of the self made vaginal vaginal devices, made out of sand, jute and fruit seed residue worn for 17-30 years is presented here which speaks of uterovaginal prolapse as gynecological morbidity. Key words: Gynecological morbidity and uterine prolapse. doi:10.3126/njog.v3i1.1444 NJOG 2008 May-June; 3(1): 58 - 59